1998
DOI: 10.1055/s-1998-1655
|View full text |Cite
|
Sign up to set email alerts
|

The Di-t-Butylphosphinyl Directed ortho Metalation Group. Synthesis of Hindered Dialkylarylphosphines

Abstract: Using the new P(O) t Bu 2 Directed Metalation Group, a variety of ortho-substituted aryl di-t-butylphenylphosphine oxides (2a-k) have been prepared, its relative metalation ability has been established, and reduction and homocoupling products (Scheme 4) have been obtained.In the realm of heteroatom-containing Directed Metalation Groups (DMGs), 3 existing phosphorus-based DMGs (Scheme 1) exhibit limitations of synthetic inaccessibility, ineffective directing ability, and competing side reactions. 4 Of particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…The syntheses of phosphinite compounds and the iridiumpincer complexes were reported previously. 4 Bis(tert-butyl)phenylphosphine oxide was prepared from di-tert-butylchlorophosphine (Strem, 96%), as described by Gray et al 11 A solution-state 31 P{ 1 H} NMR spectrum in CDCl 3 confirmed its identity (d = 51.7 ppm, s). Di-tert-butylphosphine oxide was purchased from Strem, and used as received.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The syntheses of phosphinite compounds and the iridiumpincer complexes were reported previously. 4 Bis(tert-butyl)phenylphosphine oxide was prepared from di-tert-butylchlorophosphine (Strem, 96%), as described by Gray et al 11 A solution-state 31 P{ 1 H} NMR spectrum in CDCl 3 confirmed its identity (d = 51.7 ppm, s). Di-tert-butylphosphine oxide was purchased from Strem, and used as received.…”
Section: Methodsmentioning
confidence: 99%
“…1) resembles that of an aryl(di-tert-butyl)phosphine oxide. 11 We considered the possibility that arylphosphinites undergo g-alumina-induced rearrangement to the corresponding arylphosphine oxides, which can then interact with g-alumina via the P O moiety through either adsorption onto Lewis acidic Al sites or hydrogen bonding to surface hydroxyl groups.…”
Section: Adsorption Of Phosphine Oxides Onto C-aluminamentioning
confidence: 99%
“…However these reactions could only achieve monophosphine ligands. The synthesis of 2,2'-biphenyl phosphines has relied on the Ulmann coupling of ortho-iodobenzene derivatives with the limitation of being able to synthesize only symmetric phosphine ligands [6,13,14]. In this context, 2-diphenylphosphinoyl-2'-halogenated biphenyls could open a new route for the preparation of symmetric and non-symmetric 2,2'-biphenylbased bisphosphines.…”
Section: Introductionmentioning
confidence: 99%
“…[21] Apart from this particular study, the concept of lithiation by means of directed ortho-metalation (DoM) followed by alkylation for the synthesis of new chiral organocatalysts was not further examined, although the orthodirecting properties of, for example, SO 2 NR 2 and P(O)(tBu) 2 groups are well known. [22] We found that (biaryl)hydroxyl acids (HYDRAs) can be synthesized directly from the corresponding unsubstituted disulfonimides. [23] The previously unknown compounds, for example diol 1 a, were accessed in a one-pot lithiation/alkylation sequence with bis[3,5-bis(trifluoromethyl)phenyl]methanone as an electrophile (Scheme 1).…”
mentioning
confidence: 99%